Pneumococcal glomerulonephritis in a healthy child: a case report and literature review - Ismail, Intan Hakimah; Zainudin, Zurina; Othman, Norlijah (Singapore Medical Association, 2014)
Pneumococcal glomerulonephritis is rarely described in the literature. We report a four-year-old boy who developed acute glomerulonephritis following pneumococcal bacteraemia and submandibular lymphadenitis, and review the published literature. Two weeks after developing acute glomerulonephritis, the patient developed bronchopneumonia with left pleural effusion. However, by the fourth week of admission, his renal function had normalised and lung involvement resolved.